Can the draw of professional football clubs help promote weight loss in overweight and obese men? A feasibility study of the Football Fans in Training programme delivered through the Scottish Premier League. (13th September 2011) - Gray, CM; Hunt, K; Mutrie, N; Anderson, AS; Treweek, S; Wyke, S
Abstract : Objective: The UK prevalence of male obesity is among the highest in Europe. Excess weight is associated with ill-health, but while 5-10% weight loss can significantly improve future health, men are reluctant to engage in traditional weight management programmes. This study examines the potential of professional football clubs to engage overweight and obese men in weight loss. Football Fans in Training (FFIT) is a 12 week, gender-sensitised weight management and physical activity programme delivered to groups of men at Scottish Premier League (SPL) clubs. Design: A mixed-method feasibility study including a pilot randomised trial and process evaluation involving focus groups with participants and coaches delivering FFIT. Setting: Two SPL clubs: one large, city-based; one smaller, town-based. Participants 103 men, aged 35–65 years, body mass index (BMI) ≥ 27 kg/m 2, randomly assigned to the intervention (receiving FFIT immediately, N=51) or comparison group (receiving FFIT 4 months later, N=52). Main outcome measures: The primary outcomes were viability of the recruitment procedures and participant attrition. Process outcomes included acceptability of physical and questionnaire measurement to participants, and acceptability of FFIT to men and coaches. Secondary outcomes included indications of percentage weight loss at 12 weeks, and changes in independently-measured BMI, waist circumference, and self-reported physical activity, eating habits and psychological status post-programme. Results: The recruitment target (N=60) was achieved in the large, but not smaller, club, suggesting additional measures may be needed to increase participation at smaller clubs. Attrition was low; 83.5% took part in 12-week measurements. Participants were comfortable with research procedures and very positive about FFIT. The football setting proved to be a particular draw; many indicated they would not have attended a similar programme elsewhere. Similarly positive feedback was received from coaches. The intervention group achieved a mean 4.6% weight loss (SD 2.8) while the comparison group recorded a mean 0.6% weight gain (SD 2.0); and BMI and waist circumference showed a similar pattern (all p<0.001). The intervention group also reported: significant increases in self-esteem and 12-Item Short Form Health Survey (SF-12) scores, physical activity, and consumption of breakfast, fruit and vegetables; and significant decreases in consumption of burgers, pies, crisps, biscuits and chocolate (these changes were significantly different from those reported by the comparison group, p=0.001 to 0.048). Conclusion: Professional football clubs can encourage men (a traditionally hard-to-reach group) to engage in gender-sensitised weight management programmes and to make positive lifestyle changes. Follow-up assessments will determine if short-term improvements are maintained.